Gas-Induced Ion-Free Stable Radical Anion Formation of Organic Semiconducting Solids as Highly Gas-Selective Probes - Lee, Seung Heon; Oh, Byeong M.; Hong, Chan Yoo; Jung, Su Kyo; Park, Sung Ha; Jeon, Gyeong G.; Kwon, Young Wan; Jang, Seokhoon; Lee, Youngu; Kim, Dongwook; Kim, Jong H.; Kwon, O. Pil (ACS Applied Materials and Interfaces, 2019)
The formation of stabilized radical anions on organic materials in the solid state is an important issue in radical-based fundamental research and various applications. Herein, for the first time, we report on gas-induced ion-free stable radical anion formation (SRAF) of organic semiconducting solids with high gas selectivities through the use of organic field-effect transistor (OFET) gas sensors and electron spin resonance spectroscopy. In contrast to the previously reported SRAF, which requires either anionic analytes in solution and/or cationic substituents on P-electron-deficient aromatic cores, NDI-EWGs consist of an n-type semiconducting naphthalene diimide (NDI) and various electron-withdrawing groups (EWGs) that exhibit non-ion-involved, gas-selective SRAF in the solid state. In the presence of hard Lewis base gases, NDI-EWG-based OFETs exhibit enhanced conductivity (Current-ON mode) through the formation of an SRAF NDI/gas complex, while in the presence of borderline and soft Lewis base gases, NDI-EWG-based OFETs show decreased conductivity (Current-OFF mode) by the formation of a resistive NDI/gas complex. Organic semiconducting solids with EWGs exhibiting highly gas-selective solid-SRAF constitute a very promising platform for radical-based chemistry and can be used in various applications, such as highly gas-selective probes.
Keywords: Aromatic cores; Electron withdrawing group; Electron-deficient; Enhanced conductivity; Fundamental research; Naphthalene diimide; Semiconducting solids; Stable radicals; gas sensors; naphthalene diimide; organic field-effect transistor; P-electron-deficient aromatic cores; stable radical anion formation